Implementation of Legal Protection of Trade Secrets License Based on Law Number 30 of 2000 Concering Trade Secrets - Abd Thalib; Novita Rahim; Benny Akbar (Melayunesia Law, 2026)
A company's trade secret information is very important for business actors and should not be known by other companies because trade secret information has economic value and is related to the quality of products and services produced. If a trade secret violation occurs in the form of information leakage, it will be detrimental to the company. This can affect business success and you will lose profits that should be obtained. The author's research method uses a normative juridical legal research method which is limited to the study of the application of positive law that occurs in society regarding the legal protection of trade secret licenses based on Law Number 30 of 2000. Granting a license by a trade secret owner is one way to develop a company's business. Granting a license means giving permission by the trade secret owner to the licensee to use his trade secret for commercial purposes. With the consequence of providing compensation in the form of royalties to the trade secret owner. The main clauses of the license agreement that must be agreed upon by the parties include the tempus and locus of use of exclusive rights to trade secrets, the rights of the trade secret owner to the use of exclusive rights to trade secrets by the licensee, and the licensee's authority to further pass on the license rights to third parties.